Hemozoin “knobs” in Opisthorchis felineus infected liver; Parasites & Vectors; Vol. 8 - Pershina A. G. Aleksandra Gennadievna; Saltykova I. V. Irina Vladimirovna; Ivanov V. V. Vladimir Vladimirovich; Perina E. A. Ekaterina Aleksandrovna; Demin M. A.; Shevelev O. B. Oleg Borisovich; Buzueva I. I. Irina Ivanovna; Gutakovsky A. K. Anton Konstantinovich; Vtorushin S. V. Sergey Vladimirovich; Ganebnykh I. N. Iljya Nikolaevich; Krasnov V. P. Vladimir Petrovich; Sazonov A. E. Aleksey Eduardovich; et al. (2015, 2015)
Title screen